New recode of two types of interal parasites belonging to the row of Nematda and Cestoda on the fish species sardinella aurita in the Syrian marine waters. - حميشه, يارا; تغريد لايقه , (Latakia University Journal -Biological Sciences Series, 2023)
The present study aimed to isolate, classify and identified internal parasites that affecting on Sardinella aurita, Fish samples were collected from different localities from the coast of Lattakia (the Port of fisheries and Picnic and Ibn Hani), during the period between June 2022 to May 2023 , the total number of fish examined was 240 individuals. Morphological measurements were taken (Total length, Weigh, Age) then All fish were externally examined. The internal organs of all caught individuals (Pyloric caeca, Stomach, intestines, liver, gonads, swim bladder, muscles, eyes) were examined for infection with internal parasites. In this study, two types of internal parasites were isolated: First type is the Tetraphylide type that belongs to class Cestoda, it was isolated from the pyloric caeca and the second type is Anisakis sp type that belongs to class Nematoda, it was isolated from the inner wall of the intestine. During our current research, these two types were isolated at the first time from Sardinela aurita fish, where the life cycle of each parasites species was detaild.